Trauma Psikologis dalam Novel Namaku Alam Karya Leila Salikha Chudori (Pendekatan Psikologi Sastra) - Kholijah Safirah; Marselus Robot; Karolus Budiman Jama (YASIN, 2026)
The representation of psychological trauma in literary works is important to examine in order to understand the effects of political violence, social stigma, discrimination, and intergenerational trauma on individuals’ lives. This study aimed to describe the forms of psychological trauma experienced by the characters in the novel Namaku Alam by Leila Salikha Chudori and identify the symptoms of Post-Traumatic Stress Disorder (PTSD) in the character Segara Alam. The study employed a qualitative descriptive method with a literary psychology approach. The data source was the novel Namaku Alam, published by Kepustakaan Populer Gramedia. Data were collected using reading and note-taking techniques and subsequently analyzed through the stages of identification, classification, interpretation, and validation based on psychological trauma theory and the PTSD criteria in the DSM-5-TR published by the American Psychiatric Association. The results showed that the psychological trauma experienced by the characters included interpersonal trauma and attachment trauma. Interpersonal trauma was experienced by the characters Ibu, Segara Alam, Bimo, and Kenanga as a result of violence, intimidation, loss, and sociopolitical pressure. Attachment trauma was experienced by Om Aji, Bimo, and Kenanga as a result of disrupted emotional relationships with family members and significant others due to political stigma and family separation. Segara Alam also exhibited PTSD symptoms comprising intrusion, avoidance, negative alterations in cognition and mood, and alterations in arousal and reactivity. These findings confirm that the political violence of 1965 not only caused individual psychological trauma but also affected family relationships and generated intergenerational trauma. This study contributes to the development of literary psychology studies and broadens the understanding of representations of the psychological impacts of political violence and intergenerational trauma in literary works.